Energy Renovation of Social Housing: Finding a Balance Between Increasing Insulation and Improving Heating System Efficiency. (June 2019) - Van De Moortel, E; Allacker, K; De Troyer, F; Stijnen, L; Schoofs, E
Abstract: As the budget of social housing companies is limited, reducing the energy use of their housing stock to be compliant with current standards and actions plans is an important challenge. Currently social housing companies in Flanders often prefer replacing the heating system to insulating the building envelope due to the lower investment cost and easy implementation. However, the investment in better heating systems has to be repeated several times during the service life of the building. This paper provides insights in the investment cost and life cycle cost of both renovation strategies. Moreover an environmental life cycle assessment provides insights in the environmental impact of the renovation strategies. The analysis reveals that it is recommended to replace heating boilers not earlier than at the end of their technical service life, both from an environmental and economic perspective. Sensitivity analyses show that changes in the estimated remaining building service life and increasing discount rate lead to changes in the life cycle costs but have no influence on the ranking of the renovation scenarios. Changes in the energy price, insulation level and original building type lead to changes in the costs and ranking of the renovation scenarios.